2005
DOI: 10.1007/s00216-005-3176-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ochratoxin A content from must to wine in Port Wine microvinification

Abstract: To study the evolution of ochratoxin A (OTA) content from must to wine during the making of Port Wine, grapes from the five most common varieties of Port Wine were harvested and combined in equal percentages in order to perform microvinifications. Three sets of assays were studied: a blank (A), where the most common Port Wine-making process was used; in the second (B), a solution of OTA was added to the initial must; in the third (C), the grapes were aspersed with an inoculating solution of OTA-producing fungi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 48 publications
1
30
0
1
Order By: Relevance
“…The range of OTA content in wines produced in Europe varied between 0.01 and 3.4 µg/L 4 . Values higher than 0.5 µg/L were reported by several authors 10,26,28,30 . In the winemaking process, OTA must be considered a principal safety hazard and the occurrence of this toxin in wine must be systematically investigated 15 .…”
Section: Introductionmentioning
confidence: 68%
“…The range of OTA content in wines produced in Europe varied between 0.01 and 3.4 µg/L 4 . Values higher than 0.5 µg/L were reported by several authors 10,26,28,30 . In the winemaking process, OTA must be considered a principal safety hazard and the occurrence of this toxin in wine must be systematically investigated 15 .…”
Section: Introductionmentioning
confidence: 68%
“…During this time the mycotoxin level diminishes, probably due to its adsorption on the Saccharomyces yeast surface, to its interaction with metabolites produced by yeast or its degradation by the lactic bacteria still present in wine [284][285][286]. Grape washing, cooking and pressing can also promote the OTA content drop [53,287]. During vine fruits production, efficient drying and turning over are required because in these stages, moisture and sugar content stimulates Aspergillus section Nigri development and OTA synthesis [288].…”
Section: Microbiological Methodsmentioning
confidence: 99%
“…This procedure also provides that the characteristic alcohol level of this beverage is achieved, since the fermentation was terminated. In this way, enological practices influence the concentration of OTA (PIETRI et al, 2001;BELLI et al, 2004;RATOLA et al, 2005;CHIODINI et al, 2006). VALERO et al (2008) found high levels of OTA in wines produced using grapes with excessive degree of ripeness (15.62ng ml -1 ) and fortified wines (27.79ng ml -1 ) elaborated with grape wine distillate.…”
Section: Introductionmentioning
confidence: 97%